RECOGNITION AS A FUNCTION OF MEASUREMENT IN THE REALIZATION CONCEPT. - Arnett, Harold E. (The Accounting Review, 1963)
The article determines the relationship between recognition of revenue and measurement of revenue. It has been stated that in accounting for revenue, the two central questions are the timing of revenue recognition and the determination of amount. This statement apparently implies that revenue will never be recognized before the amount can be determined but, under certain conditions, revenue will not be recognized even when the amounts can be accurately determined. The recording procedure is followed normally, not because there is difficulty in measuring revenue accurately but because it is often not possible to accurately estimate the expenses to be incurred from date of contract until final collection is made. Thus, revenue realization is made dependent upon income realization. The statement since it indicate that the goal of accounting is to reflect accurately entity economic activity as it takes place, in order to best serve the needs of statement users, might be interpreted as suggesting that the recognition of revenue should be considered a function of measurement, rather than a central question in accounting for revenue.